Krytyczna Świadomość Językowa i Pozytywna Analiza Dyskursu. Edukacyjne implikacje krytycznie zorientowanych teorii dyskursu - Karolina Starego (Problemy Wczesnej Edukacji)
Despite the growing popularity of discourse theory and critical analysis of interrelations between education and its social, political and cultural contexts, neither the “discursive” nor “linguistic” turn in social sciences are usually thought of as possible foundations for pedagogical practice. The aim of this paper is to review the possible educational applications of two critical discourse theories: Critical Language Awareness and Positive Discourse Analysis. Both of those perspectives aim to go beyond the purely research oriented modes of analysis, towards constructive and positive projects of critical language education. Thus, they may provide us with a foundation for a critically oriented pedagogy of language.